The Development of Idiom Knowledge Across the Lifespan - Sprenger, Simone A.; la Roi, Amélie; van Rij, Jacolien (Frontiers in Communication, 2019)
Knowledge of multi-word expressions, such as break the ice, is an important aspect of language proficiency that so far we have known surprisingly little about. For example, it is largely unknown how much variability there is between speakers with respect to the number of different items that they know, or what factors contribute to their acquisition. This lack of knowledge seriously limits the generalizability of experimental studies on the production and comprehension of multi-word expressions (usually idioms) and generally suggests that there still is a sizable unknown territory of language knowledge to explore. Here, we present the results of two familiarity ratings for a large sample of Dutch idioms and a large number of participants that varied in age between 12 and 86 years old. The data show considerable variation between participants and between idioms. Nonlinear mixed-effects regression analyses revealed that the age of participants, but not their education, as well as the frequency and decomposability of the idioms influenced the familiarity scores. Our findings suggest that the knowledge of multiword expressions develops across the lifespan, is acquired from exposure, and - in participants younger than about 40 years of age - varies with item decomposability.